2012
DOI: 10.1007/s11064-012-0904-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment In vitro of Retinal Cells with IL-4 Increases the Survival of Retinal Ganglion Cells: The Involvement of BDNF

Abstract: Interleukin 4 (IL-4) is a pleiotropic cytokine involved in many functions during the development as well as in adult life. Previous work from our group demonstrated, in vitro, that this interleukin is able to prevent rat retinal ganglion cells death after axotomy. The aim of the present study was to investigate the signaling pathways involved in this trophic effect, particularly the cAMP pathway and also to demonstrate the expression of IL-4 in retinas at different stages of post natal development. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
2
6
0
1
Order By: Relevance
“…We already know that M3 mAChR and IL-4 levels increase during retinal development (Araújo-Martins et al 2013;Braga et al 2013) and in the present work we show that IL-4 increases the levels of this muscarinic receptors mimicking what occurs during the normal development. Taken together, the results presented in this study demonstrate the influence of IL-4 in differentiation process of cholinergic cells from neonatal rat retina and suggests an important role for this cytokine in the development of cholinergic phenotype in the retinal tissue.…”
Section: Cell Mol Neurobiolsupporting
confidence: 82%
See 2 more Smart Citations
“…We already know that M3 mAChR and IL-4 levels increase during retinal development (Araújo-Martins et al 2013;Braga et al 2013) and in the present work we show that IL-4 increases the levels of this muscarinic receptors mimicking what occurs during the normal development. Taken together, the results presented in this study demonstrate the influence of IL-4 in differentiation process of cholinergic cells from neonatal rat retina and suggests an important role for this cytokine in the development of cholinergic phenotype in the retinal tissue.…”
Section: Cell Mol Neurobiolsupporting
confidence: 82%
“…5a). However, our group had already shown that treatment with IL-4 for 15 min induces an increase in the levels of phosphor-CREB (Araújo- Martins et al 2013). Treatment of human astrocytoma with carbamylcholine, a non-hydrolysable analog of Ach, induces NFjB activation and this effect was mediated by M3 mAChRs activation, calcium mobilization, and activation of PKC (Guizzetti et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the altertion of BDNF and NGF appears to be mediated by skewing the Th1/Th2 balance toward Th2 type by inhibition of IFN‐γ and enhanced IL‐4 production in the CNS of EAE (Villoslada et al, ; Arredondo et al, ; Makar et al, ). IL‐4 treatment increases BDNF expression in retinal ganglion cells of newborn rat culture and there is an increased production of mRNA for BDNF when astrocytes are incubated with IL‐4, which suggest that BDNF is the neurotrophin involved in IL‐4 effect (Kerschensteiner et al, ; Derecki et al, ; de Araujo‐Martins et al, ). IL‐4 has also been shown to increase the synthesis of NGF by astrocytes, lymphocytes, and C6 glial cells (Brodie and Goldreich, ; Brodie et al, ; Arredondo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction through IL-4Rs involves 3 major pathways: JAK-STAT6, Raf-MEK-ERK and PI3K-Akt [1,3]. Several studies have pointed out the role of IL-4 in different processes of brain development such as neuronal survival [7,8], proliferation [6], differentiation [6,9], and synaptic plasticity [10]. However, the impact of an anti-inflammatory cytokine in the organization of central connections has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%